Oddziaływanie przemysłu na środowisko na obszarze Rzeszowa - Gładosz, Magdalena (My University, 2012)
The master thesis is about analysis of environment state of the Rzeszów city area. Mainly focused on the atmospheric air and water estimation. Threat from noise and generated waste has been described. Benefits taken from natural environments by defined corporations has been presented. Moreover, information about ekological action has been inserted. Finally, occurs that industries are not mainly threat for natural environment of the city vicinity. It has been proved that the worst problem is surface and line emission.

Praca magisterska dotyczy analizy stanu środowiska na obszarze miasta Rzeszowa. Głównie dokonano oceny stanu powietrza atmosferycznego oraz wód. Omówiono zagrożenie hałasem oraz wytwarzanymi odpadami. Dla wybranych zakładów przemysłowych przedstawiono ich zakres korzystania ze środowiska oraz podjęte działania proekologiczne. Ostateczna analiza wykazała, że to nie przemysł jest głównym zagrożeniem dla środowiska naturalnego na obszarze miasta ale emisja liniowa i powierzchniowa.
Environmental impact of industry in the Rzeszów area
Keywords: przemysł; stężenie; emisja; technologia; zanieczyszczenie; industry; concentration; emission; technology; pollution